Post-Transplantation Cyclophosphamide-Based Haploidentical Transplantation as Alternative to Matched Sibling or Unrelated Donor Transplantation for Hodgkin Lymphoma: A Registry Study of the Lymphoma Working Party of the European Society for Blood and Marrow Transplantation - Martínez, Carmen; Dreger, Peter (Journal of clinical oncology, 2017)
PurposeTo compare the outcome of patients with Hodgkin lymphoma who received post-transplantation cyclophosphamide-based haploidentical (HAPLO) allogeneic hematopoietic cell transplantation with the outcome of patients who received conventional HLA-matched sibling donor (SIB) and HLA-matched unrelated donor (MUD).Patients and MethodsWe retrospectively evaluated 709 adult patients with Hodgkin lymphoma who were registered in the European Society for Blood and Marrow Transplantation database who received HAPLO (n = 98), SIB (n = 338), or MUD (n = 273) transplantation.ResultsMedian follow-up of survivors was 29 months. No differences were observed between groups in the incidence of acute graft-versus-host disease (GVHD). HAPLO was associated with a lower risk of chronic GVHD (26%) compared with MUD (41%; P = .04). Cumulative incidence of nonrelapse mortality at 1 year was 17%, 13%, and 21% in HAPLO, SIB, and MUD, respectively, and corresponding 2-year cumulative incidence of relapse or progression was 39%, 49%, and 32%, respectively. On multivariable analysis, relative to SIB, nonrelapse mortality was similar in HAPLO (P = .26) and higher in MUD (P = .003), and risk of relapse was lower in both HAPLO (P = .047) and MUD (P < .001). Two-year overall survival and progression-free survival were 67% and 43% for HAPLO, 71% and 38% for SIB, and 62% and 45% for MUD, respectively. There were no significant differences in overall survival or progression-free survival between HAPLO and SIB or MUD. The rate of the composite end point of extensive chronic GVHD and relapse-free survival was significantly better for HAPLO (40%) compared with SIB (28%; P = .049) and similar to MUD (38%; P = .59).ConclusionPost-transplantation cyclophosphamide-based HAPLO transplantation results in similar survival outcomes compared with SIB and MUD, which confirms its suitability when no conventional donor is available. Our results also suggest that HAPLO results in a lower risk of chronic GVHD than MUD transplantation.
Gesehen am 26.04.2018